Cryptography and Steganography Based on Hybrid Edge Detection and LSB Comparing with Traditional LSB (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Nowadays the rapid growth of internet and digital communications has been required to be protected from unauthorized users. It is important to secure the information transmitted between the sender and receiver over the communication channels such as the internet, since it is an open environment. This paper proposed an algorithm of two layers of security against attackers, which are cryptography and Steganography for sending information in secrete way. In cryptography, we are using affine hill cipher method; while in steganography we are using Hybrid edge detection with Least Significant Bit (LSB) to hide the message. We combined the two edge detectors which are canny and Laplacian of Gaussian to get the hybrid edge area in the cover image. Our paper shows how we can use edge pixels of the image to hide the bits of the secrete message using LSB method instead of using traditional LSB method.